2007
DOI: 10.3141/2023-08
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Lane Width to Safety on Urban and Suburban Arterials

Abstract: This research investigates the relationship between lane width and safety for roadway segments and intersection approaches on urban and suburban arterials. The research found no general indication that the use of lanes narrower than 3.6 m (12 ft) on urban and suburban arterials increases crash frequencies. This finding suggests that geometric design policies should provide substantial flexibility for use of lane widths narrower than 3.6 m (12 ft). Inconsistent results were found which suggested increased crash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 2 publications
1
37
0
Order By: Relevance
“…The crash modification factors involve the lane width, shoulder width, shoulder type, horizontal curves, grades, road density, two-way leftturn lanes, passing lanes, roadside design for highways and deviation angle, traffic control, individual left-and rightturn lanes, sight distance, and straight line for intersections. Potts et al [13] investigated the relationship between lane width and road safety. Their results indicate that reducing the lane width of urban and suburban road below 3.65 m increased crash frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The crash modification factors involve the lane width, shoulder width, shoulder type, horizontal curves, grades, road density, two-way leftturn lanes, passing lanes, roadside design for highways and deviation angle, traffic control, individual left-and rightturn lanes, sight distance, and straight line for intersections. Potts et al [13] investigated the relationship between lane width and road safety. Their results indicate that reducing the lane width of urban and suburban road below 3.65 m increased crash frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, when speed distribution was high, the examined vehicles tended to change lanes frequently due to the difference in speeds between vehicles. Some previous studies have found speed variations to be positively related to crashes [44,45,47,68].…”
Section: Effect Of Desired Speed Distribution On Lane Change Frequencymentioning
confidence: 92%
“…A free lane change considers a lane change of a vehicle to obtain speed advantages or more space [43]. Some previous studies have focused on the relationship between speed variations and crash rates or crash risk [19,31,[44][45][46][47], while other studies have examined the number of lane changes under different traffic flow parameters to analyze the capacity of multilane roads [39,[48][49][50]. However, these studies lacked research specifically regarding the identification and quantification of significant traffic parameters that affect lane changing using real data by considering lane changing as one of the essential subjects of sustainable traffic safety.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, motorcycle accidents increase as a result of increasing traffic volume (Radin et al, 2000). Concerning lane widths, studies have reported that roadways with narrower lanes resulted in more crash incidents (Harwood et al, 2000;Potts et al, 2007;Zegeer et al, 1988). In addition, Heimbach et al (1983) showed that collisions increase as lane widths decrease but the relationship is not linear.…”
Section: Effects Of Vehicle Speed Traffic Volume and Lane Width On Cmentioning
confidence: 96%